Evaluation of Balance Disorders in Parkinson's Disease Using Simple Diagnostic Tests—Not So Simple to Choose - Krzysztoń, Karolina; Stolarski, Jakub; Kochanowski, Jan (Frontiers in Neurology, 2018)
Background Balance disorders are one of the main symptoms in Parkinson’s Disease (PD) – patients have a tendency to fall, related traumas and also a significant restriction of mobility. Numerous tools may be used to evaluate the balance, but it is difficult to choose the proper one. The aim of this review was to compare simple diagnostic tools for PD and emphasize those characterized by a high reliability and sensitivity. Methods The global literature search was conducted in PubMED, Scopus, Science Direct, Web of Science, Cochrane and Google Scholar for publications in English and Polish from January 2007. Results According to the literature nine scales and functional tests in which clinimetric properties had been assessed in PD population were selected and described. Conclusion Basing on current knowledge, psychometric properties and clinical experience, the authors suggest the BESTest with its shortened versions and the Fullerton Advanced Balance Scale to be used for comprehensive balance assessment of Parkinson’s disease patients. These tests are easy in administration, not time-consuming and provide a professional diagnosis allowing to plan individual therapy for the patient being examined.